ANTHROPONYMY AS A BRANCH OF ONOMASTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article states that an anthroponym is a personal name, a characteristic of the individualization of an object: that each object (person) of a nomination has a name. It is further stated that the Register of names is limited, that personal names are duplicated, which is forced to give an additional name. The article claims that in a developed society, the official name of a person has the formula of his name.